MT1-MMP: a key regulator of cell migration in tissue. - Itoh, Y (2006)
Controlled cell migration is a fundamental and critical event in many physiological processes. However once control is lost, cell migration facilitates disease progression such as seen in cancer metastasis, atherosclerosis, and rheumatoid arthritis. One of the critical proteinases involved in cell migration is membrane-type 1 matrix metalloproteinase (MT1-MMP/MMP-14). MT1-MMP degrades extracellular matrix to make a path for cells to migrate, sheds cell surface molecules to give migratory signals, and activates ERK (extracellular signal-regulated protein kinase) enhancing cell migration. For MT1-MMP to promote cell migration, it needs to act in co-ordination with other cell migration machinery. Understanding such regulatory links may provide insights into the development of novel disease therapies.